Peran Vital Kemampuan Bahasa Indonesia Yang Tepat Dalam Pembelajaran Himpunan Matematika Bagi Peserta Didik - Ika Febriana; Fuji Winanti; Mikolis Etimanta Ginting; Rizky Saputra Tobing; Usnul Marisa Siregar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the role of good use of Indonesian in the learning process for students, especially in mathematics set material. Apart from that, this research also aims to reveal various theories that are relevant to the problem being researched, and is carried out by re-analyzing data that has been collected from other research results in order to prove the correctness of the data and its validity based on the title of the research. The scope of this research is to measure students' understanding using good Indonesian regarding understanding elements in mathematical set material. The research method used is quantitative research. From the research that has been carried out, it can be seen that every reference used in this research states that the use of Indonesian plays a very important role in the learning process for students.